2015
DOI: 10.1002/bab.1394
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of a new sn‐1,3‐regioselective triacylglycerol lipase from Malbranchea cinnamomea

Abstract: The thermophilic ascomycetous fungus Malbranchea cinnamomea produces lipases (EC 3.1.1.3) that allow it to grow efficiently on medium containing triacylglycerol substrates such as plant oils or tributyrin as sole carbon source. In the transcriptome of M. cinnamomea grown on olive oil, we found one cDNA sequence encoding a putative extracellular lipase. This gene, termed as MclipA, was cloned and heterologously expressed in Pichia pastoris. The recombinant protein, rMclipA, catalyzed the hydrolysis of short-cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 65 publications
0
4
0
Order By: Relevance
“…On the other hand, Lotrakul and Dharmsthiti [17] stated that if the lipase is sn -2 regiospecific, 1,3-DAGs and 1(3)-MAG might be produced. According to Tong et al [18], the TLC result obtained with Candida antarctica lipase A (CalA) displayed a clear 1,2- (2,3-) diolein spot and a slightly more intense spot of 1,3-diolein, indicating that CalA was a sn -2 regioselective lipase. For this study, similar scenario can also be observed on the TLC plate in Lanes 4–6 of Figure 4, showing a significant amount of 1,3-DAGs, and less of 1,2- (2,3-) DAGs.…”
Section: Resultsmentioning
confidence: 99%
“…On the other hand, Lotrakul and Dharmsthiti [17] stated that if the lipase is sn -2 regiospecific, 1,3-DAGs and 1(3)-MAG might be produced. According to Tong et al [18], the TLC result obtained with Candida antarctica lipase A (CalA) displayed a clear 1,2- (2,3-) diolein spot and a slightly more intense spot of 1,3-diolein, indicating that CalA was a sn -2 regioselective lipase. For this study, similar scenario can also be observed on the TLC plate in Lanes 4–6 of Figure 4, showing a significant amount of 1,3-DAGs, and less of 1,2- (2,3-) DAGs.…”
Section: Resultsmentioning
confidence: 99%
“…The molecular weight of lipases is in the range of 19–60 kDa and reported to be monomeric protein. The position of the fatty acid in the glycerol backbone, chain length of the fatty acid, and its degree of unsaturation are the factors and the physical properties of lipases depend on it [ 51 , 52 ]. The sensory and nutritive values of given triglyceride also affected by these features.…”
Section: Historical Backgroundmentioning
confidence: 99%
“…Lipases are a particular class of enzymes with a vast industrial application range and that can be used in the synthesis of glycerol-derived products [21]. They present great versatility, being used in a range of industrial reactions, such as asymmetric esterification and transesterification, aminolysis, asymmetric hydrolysis, among others [3,13,19,[22][23][24][25][26][27][28][29][30][31][32][33][34].…”
Section: Introductionmentioning
confidence: 99%